Biallelic Heterozygous Mutations in Crumbs Homolog-1 Gene Associated With Macular Retinoschisis and Angle-Closure Glaucoma: A Case Report and Literature Review - Sun, Jia-Xing; Yan, Hong-Xiang; Hu, Dan; Zhou, Jian; Wang, Yu-Sheng; Wu, Jing; Song, Xiao-Jin; Hou, Xu (Frontiers in Ophthalmology, 2022)
Background Mutations in the Crumbs homolog-1 (CRB1) gene are associated with a variety of retinal degenerations including Leber congenital amaurosis (LCA) and retinitis pigmentosa (RP). It is also important to highlight atypical features to make proper diagnosis and treatment. Case Presentation We present the case of a 7-year-old girl with biallelic heterozygous CRB1 mutations. The clinical features include macular retinoschisis, Coats-like vasculopathy, short axial length, and angle-closure glaucoma (ACG). We also briefly review the current opinion on CRB1 mutation-related diseases. Conclusion CRB1 mutations could result in a combined manifestation in anterior and posterior segments. This case emphasizes the importance of genetic diagnosis for those young patients with complicated rare clinical features to call for a specific treatment and follow-up plan. It also highlights the crucial role of CRB1 in eyeball development.